The Influence Of Delivery Speed And Purchase Experience On Online Repurchase Intention In E-Commerce Shopee User Students In Pontianak City With Trust As An Intervening Variable - Anggara, Bintang; Fachri, Helman (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The purpose of this study was to examine the effect of delivery speed and purchase experience on online repeat purchasing intentions among students who use Shopee e-commerce in Pontianak city, with trust as the intervening variable. The growth of E-Commerce in Indonesia which continues to grow indicates changes in people's behavior in meeting their needs. From the results of this study, the Adjusted R-Square value on the Trust variable (Y1) is 0.677, which means that the Trust variable (Y1) is simultaneously influenced by the Speed of Delivery (X1) and Purchasing Experience (X2) variables by 67.7%, and the remaining 32.3% is influenced by other variables outside this research model and the Adjusted R-Square Value on the Repurchase Intention (Y2) variable is 0.729, which means that the Repurchase Intention (Y2) variable is simultaneously influenced by the Delivery Speed (X1), Purchase Experience (X2) and Trust (Y1) by 72.9%, and the remaining 27.1% is influenced by other variables outside of this study. The results showed that delivery speed has a positive and significant effect on trust (T-Statistic = 3,507, P-Value = 0.000), and purchase experience also has a positive and significant effect on trust (T-Statistic = 9,940, P-Value = 0.000). In addition, trust has a positive and significant effect on repurchase intention (T-Statistic = 2.081, P-Value = 0.038), and speed of delivery also has a direct effect on repurchase intention (T-Statistic = 2.431, P-Value = 0.015). However, the purchase experience has no direct effect on the intention to repurchase (T-Statistic = 1.112, P-Value = 0.267). Finally, delivery speed has no indirect effect on repurchase intention through trust (T-Statistic = 1.746, P-Value = 0.081), while purchase experience has a significant indirect effect on repurchase intention through trust (T-Statistic = 2.018, P-Value = 0.044). Recommendations for future research include expanding the sample to include more e-commerce users in various regions and platforms, as well as testing other factors that can influence repurchase intentions, such as product quality, customer service, and price factors.